Antimicrobial resistance, biofilm production and invasion of mammary epithelial cells by Enterococcus faecalis and Enterococcus mundtii strains isolated from bovine subclinical mastitis in Brazil - Rodrigues, D. S.; Lannes-Costa, P. S.; Santos, G. S.; Ribeiro, R. L.; Langoni, H.; Teixeira, L. M.; Nagao, P. E. (Oxford University Press (OUP), 2022)
Members of the genus Enterococcus are among the most relevant etiologic agents of bovine clinical and subclinical mastitis, a major problem for the dairy industry. In Brazil, clonal diversity, and multidrug resistance profiles related to bovine infections need further investigation. In this study, 11 bacterial strains recovered from mastitis subclinical cases detected in different farms of São Paulo, Brazil, were identified as Enterococcus faecalis (n = 8) and Enterococcus mundtii (n = 3) by biochemical testing and MALDI-TOF mass spectrometry. Pulsed-field gel electrophoresis categorized the enterococcal isolates into two main clusters (A and B) with similarity ranging from 85 to 100%. The isolates were shown to be resistant tetracycline (73%), erythromycin (73%), quinupristin–dalphopristin (64%), norfloxacin (9%), fosfomycin (9%) and linezolid (9%). Moreover, seven strains (64%) were considered multidrug-resistant. All the isolates were able to produce biofilms when grown in milk for 24 h: 54·54% were classified as moderate producers and 45·45% were weak producers. Interestingly, only two strains (Ef17 and Em42) remained as moderate biofilm producers after 48 h incubation. Moreover, all isolates showed no ability to form biofilm in tryptic soy broth (TSB) after 24 and 48 h incubation. In addition, cytoskeleton components were partially involved in E. faecalis and E. mundtii entry to epithelial cells as demonstrated by induction of actin stress fibre. In conclusion, enterococci isolates recovered from bovine subclinical mastitis were resistant to several classes of antibiotics, showing the ability to form biofilms in milk and invade mammary epithelial cells, suggesting an advantageous feature in mammary gland colonization during mastitis development. In addition, they can spread along the food chain by different routes and eventually constitute a possible threat for public health, including E. mundtii specie.
Keywords: biofilm; Enterococcus faecalis; Enterococcus mundtii; MAC-T cells